Feasibility of delivering supervised exercise training following surgical resection and during adjuvant chemotherapy for pancreatic ductal adenocarcinoma (PRECISE): a case series - Malcolm Brown; Dominic O'Connor; Richard Turkington; Martin Eatock; Rebecca Vince; Claire Hulme; Roy Bowdery; Rebecca Robinson; Jonathan Wadsley; Anthony Maraveyas; Gillian Prue (BMC, 2023)
Abstract Introduction Pancreatic ductal adenocarcinoma (PDAC) is an aggressive neoplasm, with surgical resection and adjuvant chemotherapy the only curative treatment. Treatment-related toxicities place a considerable burden on patients although exercise training has shown promise is helping to manage such adversities and facilitate rehabilitation. The feasibility and safety of exercise training as a supportive therapy during adjuvant chemotherapy remains unknown. Methods Patients with PDAC were screened post-surgical resection and enrolled in a 16-week, progressive, concurrent exercise programme alongside their chemotherapy regimen. Feasibility was the primary objective detailing recruitment, retention and adherence rates throughout as well as the safety and fidelity of the intervention. Secondarily, the impact on functional fitness and patient-reported outcomes was captured at baseline, post-intervention and 3-month follow up. Results Eight patients consented to participate in this trial, with five proceeding to enrol in exercise training. Concurrent exercise training is feasible and safe during adjuvant chemotherapy and prevented an expected decline in functional fitness and patient-reported outcomes during this time. Discussion This case series provides preliminary evidence that concurrent exercise training during adjuvant therapy is safe, feasible and well tolerated, preventing an expected decline in functional fitness, muscular strength and health-related quality of life (HRQoL). Given the adverse effects of treatment, these findings are promising and provide further evidence for the inclusion of exercise training as a standard of care for surgical rehabilitation and managing treatment-related toxicities. Future research should explore the impact of exercise training during neoadjuvant chemotherapy, with prehabilitation now standard practice for borderline resectable disease. Trial registration ClinicalTrials.gov Identifier: NCT04305067, prospectively registered 12/03/2020, https://classic.clinicaltrials.gov/ct2/show/NCT04305067 .